Patologi Birokrasi Dalam Pengelolaan Tenaga Honorer Di Kabupaten Mamuju Tengah - Sampar Sampar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to examine and analyze the bureaucratic pathology model in the management of honorary staff in Central Mamuju. Some of the indicators used in this study include perceptions of managerial style, violation of legal norms, low knowledge and skills, dysfunctional behavior and internal situations in various government agencies. The research method used is qualitative by using interviews as a means of extracting secondary data. Information is obtained from local governments, namely the education office, regional civil service agencies, financial institutions, council secretariats, hospitals and honorary staff. The results showed that the management of honorary staff in Central Mamuju district still shows bureaucratic pathology. This is evident in the method of recruiting honorary staff, there are still some individuals who still practice nepotism towards the acceptance of honorary staff; the lack of discipline of honorary staff is part of the pathology of the bureaucracy. Furthermore, the discipline of honorary staff in several OPDs is still not effective; found data dissynchronization / administration mall. Data discrepancies between the SK data issued and the data on the amount of wages disbursed by regional finances; the potential for budget fattening due to the absence of data validation from financial institutions on the number of SKs in each OPD with the reality in the field. Several suggestions were given as input to correct deficiencies in the management of honorary staff in Central Mamuju District.